(untitled) (World Economics and Finance Bulletin, 2026)
This study aims to examine the role of auditors in enhancing the credibility of accounting information, and to analyze the relationship between audit quality and limiting creative accounting practices that may negatively affect the credibility of financial statements. The study defines credibility and describes the most common innovative accounting practices. It also addresses the procedures and tests that auditors use to determine these practices, as well as the role of professional standards and regulatory bodies in supporting their work. The results indicate a strong correlation between auditors’ commitment to professional and ethical standards and increased confidence among financial statement users. Moreover, the study shows that professional oversight contributes to reducing practices that undermine the credibility of accounting information. Therefore, the study recommends supporting the independence of auditors, facilitating effective professional oversight, and developing standards that improve audit quality and credibility.